DFT analysis of the linkage isomerism in penta(ammine)ruthenium(II/III) complexes of benzotriazole: Natural bond orbital method approach and a comprehensive energy decomposition analysis. Issue 16 (3rd March 2019) - da Costa Gouveia, Tiago Leyser; Campos, Renan Borsoi; Ribeiro, Ronny Rocha; Nunes, Fábio Souza
Abstract : Penta(ammine)ruthenium benzotriazole complexes [Ru II/III (NH3 )5 bta] +/2+ and [Ru II/III (NH3 )5 btaH] 2+/3+ (bta and btaH are the deprotonated and neutral form of the triazole ligand, respectively) can exhibit two linkage isomers κ N1 and κ N2 . This system was investigated by density functional theory natural bond orbitals analysis and Su‐Li energy decomposition analysis. Steric, electrostatic, exchange, repulsion, polarization, and dispersion energy components of the total metal–ligand interaction were quantitatively evaluated, and revealed that the overall metal‐triazole ligand is comprised of donor–acceptor interactions like σ‐donation and π‐back‐donation, which favors a specific isomer depending on the oxidation state of the ruthenium and the charge of the ligand. Further, activation energies (Δ G ‡ ) for linkage isomerization reactions were calculated. Results were correlated with experimental chemical–electrochemical data and two plausible mechanisms are discussed. © 2019 Wiley Periodicals, Inc. Abstract : A detailed natural bond orbitals and energy decomposition analysis to address a linkage isomerization study in penta(ammine)ruthenium benzotriazole complexes was performed. The analysis included the quantification of steric, electrostatic, exchange, repulsion, polarization, and dispersion energy components of the total metal–ligand interaction.